Main Areas Improvement Of Activities And Tax Regimes Of Free Economic Zones Of Uzbekistan - RAMAZANOVICH, KUZIEV RAVSHAN (The journal of contemporary issues in business and government, 2021)
The article examines such problems as the theoretical aspects of the emergence of free economic zones and their role in the economy of the state, the formation of free economic zones, the features of the emergence and development of tax regimes, free economic zones as a category in the economy and their need for the development of the country. The article provides an analysis of domestic, their development of free economic zones and the existing tax regime, an analysis of the legal framework for the creation and functioning of free economic zones, as well as an analysis of the economic indicators of enterprises - participants in free economic zones and the tax incentives they use.